2005
DOI: 10.1097/01.hjh.0000174971.64589.39
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and health-related quality of life: an epidemiological study in patients attending hospital clinics in China

Abstract: Hypertensive individuals represent a vulnerable population that merits special attention from healthcare providers and systems. This is especially important given that low health-related quality of life can be a risk factor for subsequent cardiovascular events or complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 33 publications
6
60
2
10
Order By: Relevance
“…12 We determined that quality of life was lower in participants with controlled hypertension under drug treatment than in participants with uncontrolled hypertension using or not using BP drugs. These findings are discordant with those reported by Li et al, 32 who found higher HRQoL in controlled hypertensive patients compared with uncontrolled hypertensive patients under drug treatment. Another study showed that awareness of being hypertensive was associated with worse HRQoL.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…12 We determined that quality of life was lower in participants with controlled hypertension under drug treatment than in participants with uncontrolled hypertension using or not using BP drugs. These findings are discordant with those reported by Li et al, 32 who found higher HRQoL in controlled hypertensive patients compared with uncontrolled hypertensive patients under drug treatment. Another study showed that awareness of being hypertensive was associated with worse HRQoL.…”
Section: Discussionsupporting
confidence: 74%
“…Another study showed that awareness of being hypertensive was associated with worse HRQoL. 32 On the other hand, Erickson and associates reported lower HRQoL due to symptoms associated with drug treatment. 23 The worst quality of life of treated hypertensive individuals with controlled BP could be attributed to the more intensive treatment to control BP levels and maintenance of lifestyle changes that could adversely influence HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the recognition and control of hypertension and its effects on morbidity and mortality, the evaluation of the health related quality of life (HRQoL) has been considered another important measure of outcome in treating hypertensive patients (4) . Studies have reported worse HRQoL among hypertensive individuals compared with those without hypertension (5) , which has been attributed to factors such as adverse effects related to the pharmacological therapy (6) , stigma associated with recognition by the subject of the hypertension -called the labeling effect (7) , as well as symptoms arising from diastolic heart failure (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Como a HAS é considerada por alguns pesquisadores uma condição assintomática, particularmente nos estágios leve e moderado, suas implicações na QVRS são ainda controversas (BARDAGE; ISACSON, 2001;MENA-MARTIN et al, 2003;Li et al, 2005;BANEGAS et al, 2006).…”
Section: A Hipertensão Arterial Sistêmica E a Qualidade De Vida Relacunclassified
“…Dessa forma, a prevenção e o diagnóstico precoce e o tratamento oportuno de doenças crônicas associadas, como o DM, a dislipidemia, dentre outras, podem ser importantes para preservar a QVRS em pessoas com HAS (ZYGMUNTOWICZ et al, 2012). Outros estudos também registram que a prevenção e o tratamento adequado da HAS e comorbidades evitam uma maior deterioração da QVRS (LI et al, 2005;WANG et al, 2009).…”
Section: Tempo De Diagnóstico De Has Alterações Clínicas E Doenças Vunclassified